PROFITABILITY ANALYSIS OF YAM MARKETING IN BAUCHI STATE, NIGERIA - Ameh, B. O.; Effiong, M. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study analysed the profitability, marketing efficiency, and constraints of yam marketing in Bauchi State, a non-producing area in northeastern Nigeria. A multi-stage sampling procedure was used to select 280 yam marketers (120 wholesalers and 160 retailers) across five Local Government Areas. Data collected through structured questionnaires were analysed using descriptive statistics, marketing margin analysis, and Shepherd’s marketing efficiency ratio. Results revealed that yam marketers were predominantly male (100%), with mean ages of 36 years for retailers and 39 years for wholesalers. Profitability varied by tuber size and age; small-sized new yams yielded the highest rate of return (0.31 for retailers; 0.26 for wholesalers), while large old yams recorded lower returns (0.20 and 0.15 respectively). Purchase cost constituted over 70% of total expenses for wholesalers and over 92% for retailers. Marketing efficiency was higher in the retail subsector (efficiency index: 6.10) compared to wholesale (2.11) using the conventional method, while Shepherd’s overall marketing efficiency index was 5.6. Major constraints included inadequate marketing capital (92.5% retailers; 85% wholesalers), high transportation costs (48% retailers; 100% wholesalers), poor market infrastructure (78.1% retailers; 70.8% wholesalers), and insecurity affecting supply chains (80.8% wholesalers). The study concludes that yam marketing in Bauchi State is profitable but constrained by infrastructural, financial, and security challenges. Smaller tubers offer better investment returns due to consumer preference and affordability. To enhance marketing efficiency and sustainability, the study recommends improving rural road networks, establishing targeted credit schemes for marketers, promoting cooperative formation, and strengthening security along supply routes from major yam-producing states. These interventions are essential for ensuring stable yam supply and food security in non-producing regions.